The relationship between entrepreneurial competencies and entrepreneurial success among homestay entrepreneurs in Malaysia - Kelvin Yong; Nur Thara Atikah Zainal; Brahim Chekima (Human Resource Management Academic Research Society (HRMARS), 2021)
The purpose of this study is to examine the relationship between entrepreneurial competencies and entrepreneurial success among homestay entrepreneurs in Malaysia. The study was carried out at the state of Sabah or North of Borneo. Ever since the homestay entrepreneurs keep increasing every year in Sabah, Malaysia. However, there is still a lack of study in measuring the entrepreneurial success in the homestay contexts in Malaysia. The study applies a quantitative approach, and the respondents were selected based on purposive sampling. Only 181 useful questionnaires were collected. The finding of the study provides useful insight for academic, managerial implication and policy makers that are related to enhance the homestay industry in Sabah, Malaysia. It shows that the entrepreneurial competencies have a significant relationship towards entrepreneurial success. The Novelty of the study provides useful insight for future study, designing the most effective programme for homestay entrepreneurs, and providing empirical results for future research.